Development of Augmented Reality (AR)-based Civics Learning Media to Improve Global Diversity Character in Junior High School - Yunus, Rasid; Adhani, Yuli; Adjie, Zulfikar; Cuga, Candra (Universitas Negeri Gorontalo, 2024)
This research is motivated by the needs and challenges of secondary school students learning civics in school. So far, Civic learning is still considered a saturated subject area, which has an impact on students' learning motivation and learning outcomes. Through Augmented Reality-based learning media can promote students' global diversity insights, the learning atmosphere is more fun and meaningful. This research is more about the development of augmented reality media designs to promote the understanding of global diversity insights and their impact on students' learning atmosphere. The results showed that the development of AR-based PELAJAR learning media received a percentage of 92.3%, which was included in the